Evolution of Medical Students' Interest in Orthopaedic Surgery Careers from Matriculation to Graduation - Katherine M. Gerull, MD; Maria Pérez, MA; Cara A. Cipriano, MD; Donna B. Jeffe, PhD (JBJS Open Access, 2024)
Introduction:. Little is known about risk factors for changes in students' interest in orthopaedics during medical school. We aimed to identify variables associated with diminished (vs. sustained) and emerging (vs. no) plans to become board certified in orthopaedic surgery. Methods:. We conducted a retrospective national-cohort study of students who matriculated in US MD-granting medical schools in academic years 1993 to 1994 through 2000 to 2001. The outcome measure was the evolution of students' board-certification plans in orthopaedic surgery from matriculation to graduation using responses on the Association of American Medical Colleges' Matriculating Student Questionnaire and Graduation Questionnaire. Covariates included demographic, attitudinal, experiential, and career intention variables. Results:. Of 53,560 graduates with complete data, 2,765 students reported diminished interest in becoming board certified in orthopaedics, 1,345 reported emerging interest, and 1,327 reported sustained interest. In multivariable logistic regression models, students who were female (adjusted odds ratio [aOR] 1.83, 95% confidence interval [CI] 1.43-2.34), Asian (aOR 1.46, 95% CI 1.18-1.82), reported greater importance of social responsibility (aOR 1.16, 95% CI 1.02-1.33) and prestige (aOR 1.20, 95% CI 1.10-1.30) in choosing a medicine career, and planned full-time university faculty careers (aOR 1.58, 95% CI 1.33-1.89) at graduation were independently more likely to have diminished (vs. sustained) interest. Students who participated in research and/or authorship electives (aOR 3.50, 95% CI 3.00-4.07) and who attended private institutions (aOR 1.23, 95% CI 1.10-1.39) were more likely to have emerging (vs. no) interest. Conclusions:. Twice as many students lost interest than gained interest in orthopaedics during medical school, and the cohort of students interested in orthopaedics became less diverse over the course of medical school. Several risk factors amenable to change were identified. Interventions that target these risk factors are warranted to increase the diversity of the orthopaedic surgery workforce.